The Forgotten Quail Decline: The Plight of Scaled Quail in Texas - Fidel Hernandez; Chad J. Parent; Ian C. Trewella; Eric D. Grahmann (National Quail Symposium Proceedings, 2017)
Several quail species are experiencing range-wide declines in the United States. The northern bobwhite (Colinus virginianus) has garnered the most attention, both from a research and conservation perspective. The bobwhite decline in Texas, has resulted in considerable time and effort being devoted to research and management on the species due to its status as a highly popular and economically important game bird. This attention has been beneficial to bobwhite conservation and management but, an unfortunate consequence of this focus has been neglect of the scaled quail (Callipepla squamata) that has been declining at even a more alarming rate. Scaled quail, according to Breeding Bird Survey (BBS) data, have declined at a rate of 5.1% per year in the Tamaulipan Biotic Province (southern Texas), the greatest of any region surveyed in its geographic range. Anecdotal reports of landowners have long noted the gradual disappearance of scaled quail and concomitant replacement with northern bobwhite throughout southern Texas, beginning since about the 1990s. Analysis of BBS data provides evidence for this replacement. Percent of quail detections in the core of the scaled quail range in the Tamaulipan Biotic Province were 80:20 (scaled quail: bobwhite) during the 1960s but currently represent about 5:95. In addition, the range of scaled quail has been contracting, moving progressively west with time. The species is no longer detected on the easternmost BBS routes in southern Texas.
Keywords: Breeding Bird Survey data; Callipepla squamata; Colinus virginianus; northern bobwhite; scaled quail